2022
DOI: 10.1155/2022/7497500
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Disease Severity and Outcome of Severe Acute Respiratory Syndrome Coronavirus 2 and Influenza Viruses Coinfection Seen at Egypt Integrated Acute Respiratory Infections Surveillance, 2020–2022

Abstract: Background. Cocirculation of influenza (Flu) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (SARS-CoV-2/Flu) represent a public health concern as it may worsen the severity and increase fatality from coronavirus disease 2019. An increase in the number of patients with coinfection was recently reported. We studied epidemiology, severity, and outcome of patients with SARS-CoV-2/Flu coinfection seen at Egypt’s integrated acute respiratory infections surveillance to better describe disease impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Coinfection with influenza and SARS-CoV-2 was reported in Egypt before and led to more severe course and outcomes compared to a single viral infection 9 , 34 . Similarly, this study reported coinfection with more than one viral cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coinfection with influenza and SARS-CoV-2 was reported in Egypt before and led to more severe course and outcomes compared to a single viral infection 9 , 34 . Similarly, this study reported coinfection with more than one viral cause.…”
Section: Discussionmentioning
confidence: 99%
“…Acute respiratory infections (ARIs) are a leading cause of morbidity and mortality among children under five, particularly in developing countries, and pose a major threat to healthcare systems 8 . In Egypt, ARIs are monitored through integrated surveillance for ARI, National Disease Surveillance System for communicable diseases (NEDSS), ARI syndromic surveillance, ARI mortality surveillance, and event-based surveillance systems (EBS) 9 . ARI's integrated surveillance system monitors the activity of influenza and SARS-CoV-2 at 12 influenza like illness (ILI) and 17 severe acute respiratory infections (SARI) sentinel sites located in 19 governmental hospitals, plus the Central Public Health Laboratory (CPHL) and a network of five regional laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a large amount of clinical evidence indicating that co-infection with COVID-19 and influenza increases the risk of patient mortality and prolongs hospitalization ( Dadashi et al., 2021 ; Garg et al., 2022 ; Cong et al., 2022 ; Fahim et al., 2022 ; Musuuza et al., 2021 ). In patients with co-infections, the risk of death is around twice as high as in those with COVID-19 infection alone ( Stowe et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%